2006
DOI: 10.1111/j.1464-410x.2006.06056.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of serotonin and serotonin antagonists on bladder cancer cell proliferation

Abstract: cancer tissue was determined by immunohistochemistry and Western blot analysis. RESULTS5HT caused a dose-dependent increase in the proliferation of HT1376 cells. The maximum increase in cell proliferation (12%; 12 samples, P < 0.001) was at 10 − 8 M as compared to the control at 72 h. At 10 − 4 M , 5HT 1A antagonist and 5HT 1B antagonist (SB224289 hydrochloride) had a 10% (12 samples, P < 0.001) and 93% (12, P < 0.001) inhibitory effect on HT1376 cell growth, respectively, compared to the control at 72 h. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 51 publications
2
64
0
1
Order By: Relevance
“…Serotonin was previously shown to be mitogenic in different cancer cell lines (13)(14)(15). In line with these reports, colon cancer cell lines CT-26 and MC-38 showed increased proliferative activity when exposed to serotonin in vitro.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Serotonin was previously shown to be mitogenic in different cancer cell lines (13)(14)(15). In line with these reports, colon cancer cell lines CT-26 and MC-38 showed increased proliferative activity when exposed to serotonin in vitro.…”
Section: Discussionsupporting
confidence: 78%
“…Accordingly, antagonists for serotonin receptors 1A and 1B reduced the proliferation rate of bladder cancer cells in vitro (15). However, in vivo studies investigating the function of serotonin in cancer growth and progression are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The mitogenic eVect of 5-HT on HT29 cells may be dependent on the presence of serum and its interaction with other hormones or growth factors (Sharpe et al 2002;Sonier et al 2006). In support of our study, previous investigations have suggested that 5-HT increases the growth rate of HT1376 bladder cancer cells (Siddiqui et al 2006) and human prostate cancer cells (Dizeyi et al 2004). Another study has shown that the proliferative properties of 5-HT may occur due to its binding to diVerent 5-HT receptor subtypes which are associated with cascades of mitogenic signaling pathways (Launay et al 1996).…”
Section: Discussionsupporting
confidence: 84%
“…After calculating immunoreactivity index of the receptors for each patient, we calculated mean and SD of 30 patients. Data analysis was carried out using Student's t test (Bradford 1976;Dizeyi et al 2004;Siddiqui et al 2006). …”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation